Is auditor-general the ally of the parliament and the people? / Mohd Azmi Nias Ahmad - Ahmad, Mohd Azmi Nias (Universiti Teknologi MARA Cawangan Pahang, 2005)
This paper outlines the scope of the auditor-general’s activities. It can be concluded that the activities can be divided into the three categories, financial statement audit, compliance audit and performance audit. Auditor-General’s authority to undertake examinations of the government agencies should be maintained and the Auditor-General is expected to offer recommendations for improvement not only regarding accounts and records, but in relations to management efficiency, economy and effectiveness. Four states of Audited Financial Report were reviewed in order to determine whether the Auditor-General is “the ally of the parliament and the people”.